Global Trends and Current Status in Osteonecrosis of the Femoral Head: A Bibliometric Analysis of Publications in the Last 30 Years - Wen, Zeqin; Li, Yusheng; Cai, Zijun; Fan, Meng; Wang, Jian; Ding, Ran; Huang, Cheng; Xiao, Wenfeng (Frontiers in Endocrinology, 2022)
Introduction: Osteonecrosis of the femoral head (ONFH) is a progressive and disabling disease primarily caused by long-term or excessive glucocorticoids (GCs) administration. The purpose of our study was to summarize the global trends and current status in ONFH. Materials and Methods: Publications related to ONFH from 1991 to 2020 were searched from the Web of Science (WOS) core collection database. The data were analyzed with bibliometric methods. Microsoft Excel was used to statistical analysis and draw bar charts. SPSS was applied to perform linear regression analysis. VOSviewer was used to conduct bibliographic coupling analysis, co-authorship analysis, co-citation analysis and co-occurrence analysis. Results: A total of 5,523 publications were covered. The United States consistently ranked first in total publications, sum of times cited, average citations per item and H-index. Kyushu University was the main contributor to ONFH. Clinical Orthopaedics and Related Research was the major publishing channels for ONFH-related articles. Takuaki Yamamoto published the most ONFH-related articles. Studies regarding ONFH could be divided into 5 clusters: mechanism study, treatment study, complication study, radiological study and etiological study. Mechanism study might become the hot spot in the future. Conclusions: The total publications of ONFH generally increased over time in the last three decades. The United States was the leading country in ONFH research. Mechanism study about ONFH including mesenchymal stem cells, apoptosis, oxidative stress, adipogenesis, osteogenic differentiation and endothelial progenitor cell had attracted more attention and would become the hot spot in the future.